Les réseaux d’équipements sportifs dans les stations balnéaires : l’exemple du tennis - Françoise Rollan (In Situ)
Sport facilities networks are an integral part of sport history and development in France. Starting as a snobbish activity, in one century sport became a popular phenomenon. Modern sport, going against traditional sport, met with a great many obstacles. On top of this, the legislation was not favourable since it forbade any association. Therefore the role of the State was essential. But, it was the 1901 Law concerning associations which made it truly possible for the sporting networks to be formed and for sport facilities networks to be initiated, the State taking over in a second time. On seaside resorts, the hierarchy of which was already established before WWI, the English were at the beginning of the various sports. The upper classes followed and participated actively to its spreading. Sport facilities which were private at the start had to be supported by - State. But after massive public investments during the eighties, sport facilities networks prove to be underused a major part of the year. On the opposite, the golf courses of the Atlantic, the Channel, and the North Sea Coasts seaside resorts which are network organised because they go along with property programmes, get a return all over the year.